2010
DOI: 10.1111/j.1439-0507.2009.01704.x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity ofPterocaulon alopecuroides(Asteraceae) against chromoblastomycosis agents

Abstract: Plants of the genus Pterocaulon (Asteraceae) are popularly used in the treatment of skin diseases caused by fungi and bacteria. The aim of this work was to investigate the in vitro activity of the crude methanolic extract obtained from the aerial parts of Pterocaulon alopecuroides (Lam.) against some agents of chromoblastomycosis, a chronic fungal infection of the skin and of the subcutaneous tissue caused by traumatic inoculation of the aetiological agent. The extract was active against all the strains tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…An ethnoveterinary survey indicated that plants from the genus Pterocaulon (Asteraceae) are used in Brazilian traditional medicine to treat skin diseases caused by both bacteria and fungi [2]. In recent years, various pharmacological studies conducted on the extracts of these plants have supported their ethnomedical use and the biological properties are attributed to coumarins, the most abundant compounds found in these species [3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…An ethnoveterinary survey indicated that plants from the genus Pterocaulon (Asteraceae) are used in Brazilian traditional medicine to treat skin diseases caused by both bacteria and fungi [2]. In recent years, various pharmacological studies conducted on the extracts of these plants have supported their ethnomedical use and the biological properties are attributed to coumarins, the most abundant compounds found in these species [3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Invasive pulmonary aspergillosis remains a frequently fatal complication of bone marrow transplantation and of cancer chemotherapy in patients with haematologic neoplasms 3,4 . In many cases, treatment of these invasive fungal infection diseases is hampered by the toxicity of a limited number of available antifungal agents and also resistance to these agents by fungal pathogens 5 . This situation has led to an ongoing search for fungicidal agents with different modes of action and fewer side effects and which can be administered parenterally.…”
Section: Introductionmentioning
confidence: 99%
“…Plants of the genus Pterocaulon have shown activities against different fungi, bacteria, and protozoa (Alarcón et al 2008;Ródio et al 2008;Daboit 2010). This study has demonstrated that P. polystachyum essential oil can reduce the A. polyphaga trophozoites viability.…”
Section: Discussionmentioning
confidence: 69%
“…A study of Stein and colleagues (2005) and Daboit et al (2010) showed that Pterocaulum alopecuroides, Pterocaulum balansae, and Pterocaulum polystachyum extracts were active against a range of pathogenic fungi. The hexane extract of the latter plant showed amoebicidal activity against a pathogenic strain of Acanthamoeba (Ródio et al 2008).…”
Section: Introductionmentioning
confidence: 99%